Team Psychological Safety and Voice of Nurses in Affiliated Hospitals of Guangxi University of Chinese Medicine, the People’s Republic of China - Zhong, Mengqi; Akkadechanunt, Thitinut; Chitpakdee, Bunpitcha (Biomedical Sciences and Clinical Medicine, 2022)
Objectives: To explore team psychological safety and voice of Chinese nurses and examine the relationship between team psychological safety and the voice of nurses in China. Methods: A descriptive correlational study was conducted among 422 nurses who have worked at least one year in three affiliated hospitals of Guangxi University of Chinese Medicine, the People’s Republic of China. Data collection using a set of questionnaires consist of Demographic Data Form, Team Psychological Safety Climate Scale (TPSCS), and Employee Voice Scale (EVS). Descriptive statistics and Spearman’s Rank-order Correlation were used to analyze data. Results: Nurses perceived both team psychological safety and voice at a moderate level. Team psychological safety and voice had a strong positive correlation. The dimensions of speak one’s mind freely, respect each other, interpersonal risk-taking, and mutual trust were also found to be significantly and positively associated with voice Conclusion: When nurses feel psychologically safe in their team, they are more likely to express ideas, information, and opinions which making cooperative contributions to the work unit or the hospital. These findings can guide hospitals and nursing administrators to develop strategies to improve team psychological safety which will lead to an increase in the voice of nurses.